Immunotherapy in nonmuscle invasive bladder cancer: current and emerging treatments. Issue 3 (May 2019) - Gupta, Mohit; Kates, Max; Bivalacqua, Trinity J.
Abstract : Purpose of review: There is a significant unmet need for efficacious second-line treatment options for patients who have failed bacillus Calmette-Guerin (BCG) therapy for nonmuscle invasive urothelial carcinoma (NMIBC). Recent advances in our understanding of systemic immunotherapy have transformed the management of advanced urothelial carcinoma and have led to the development of multiple novel agents. Using this insight, these agents are now being investigated for use in NMIBC. Recent findings: Although BCG has been used to treat high-risk NMIBC for decades, new applications of immunotherapy include the use of exogenous cytokines to boost immune response, vaccines to activate the immune system against specific tumor-associated antigens, intravesical agents that cause generalized local inflammation, and targeted antibodies against proteins on the surface of immune checkpoint inhibitors. Although most of these agents are still being investigated in clinical trials and are not yet considered standard of care, they hold significant promise in the treatment of patients with high-risk NMIBC. Summary: The use of immunotherapy has significantly improved survival outcomes in advanced urothelial carcinoma. Based on rapid advances in our understanding of the immune system and tumor biology, these agents are also poised to alter the therapeutic landscape for NMIBC dramatically as clinical trials are completed.